Auditoría en Seguridad Vial ruta nacional 2507. Pacífico Tres Unidad Funcional Uno del Km 15+000 Al Km 21+000. (2020)
Carry out a Road Safety Audit on the variables: containment barriers and signaling, to establish their condition vis-à-vis the road actors that circulate through it, in the section between Km 15 to Km 21 of national route 2507. Pacific Three Functional Unit One Virginia - Asia is the reason for this work. For this, some field activities are required, the objective of which is to determine the technical state of the road, to carry out a photographic inventory of the variables analyzed, and using tools such as the checklist, determine what are the constituent elements of a road that corresponds to it and they exist in this section, subsequently the accident rate of the audited section was investigated and using technical instruments such as predetermined formats and specialized software plus the information collected in the field work, risk matrices and maps that describe the degree of risk in which some the most vulnerable and affected actors are the variables that most influence it.